Factors Affecting the Clinical Measurement of Visuo-Spatial Neglect - L. Pizzamiglio; C. Bergego; P. Halligan; V. Homberg; I. Robertson; E. Weber; B. Wilson; P. Zoccolotti; G. Deloche (Behavioural Neurology)
The present study examined a battery of tests to evaluate unilateral spatial neglect; the tests included different tasks involving several modalities of spatial exploration mapping perceptual, motor, attentional and personal or extrapersonal space dimensions. The subjects, 121 right-brain-damaged patients with unilateral neglect, were studied in seven laboratories in four European countries. Relationships among the various tests were examined by correlations, a cluster analysis and by an analysis of individual cases. Different sensitivity was found among various tests for detecting neglect performances. Both the cluster analysis and the single case analysis clearly showed a segregation between personal and extrapersonal neglect. Analysis of the large cluster, including a variety of tests of extra personal neglect, together with the study of single cases, suggests the possibility of differentiating the various manifestations of spatial neglect which can be interpreted on the basis of the descriptions of other individual cases previously reported in the literature. Finally, the present study indicated the relative stability of neglect following the acute phase and its independence from age.